Теоретичне дослідження методів вдосконалення редукторів - Невдаха, Ю. А.; Дубовик, В. О.; Невдаха, А. Ю.; Nevdaha, Yu.; Dubovik, V.; Nevdaha, A. (КНТУ, 2015)
В статті проведений теоретичний аналіз методів дослідження вдосконалення редукторів. Розглянуті технологічні та конструкторські рішеня модернізації редукторів. Розглянута необхідність медернізації редукторів, внаслідок підвищення вимог до навантажувальної здатності. Запропоновано використання сучасних матеріалів при виготовлені редукторів. In article the theoretical analysis of methods of research of improvement of reducers is carried out. Considered such technological and design solutions reducers modernization as increased hardness of working surfaces of the teeth, making precision gears, gears modernization and transfers by increasing the kinematic precision manufacturing gears using higher quality materials. The necessity modernization of reducers, due to increased load capacity requirements. The use of modern materials made with gears.
Theoretical research of methods of improvement of reducers
Keywords: редуктор; корпус редуктора; вал; зубчасте колесо; зубчасті передачі; reducer; reducer case; shaft; cogwheel; tooth gearings